The problem of moral reasoning: consequentialist and deontological criteria - Da Cruz, Daniel Nery (Discusiones Filosóficas, 2018)
The text deals with the problem of moral reasoning or the criteria that allows to judge the correct from the incorrect action in the scope of ethical consequentialism and deontological morality. Once the two terms are defined, ethical utilitarianism will be taken as a classic example of moral consequentialism opposing to this perspective the Kantian deontological ethics. With these two theoretical parameters of morality, the discussion will focus on the assessment of problem cases, exploring the ethical issues they raise, evidencing the insufficiency of elucidating them only based on consequentialist principles and the moral of duty.